Pengaruh Pajak Daerah dan Retribusi Daerah Terhadap Pendapatan Asli Daerah di Kabupaten Musi Rawas - Azzahra, Virandita; Kesuma, Indrawati Mara; Andrinaldo, Arisky (Innovative: Journal Of Social Science Research, 2025)
This study aims to analyze the effect of regional taxes and regional levies on local revenue (PAD) in Musi Rawas Regency. The data used are secondary data in the form of budget realization reports from 2019 to 2023 obtained from the Musi Rawas Regency Tax and Retribution Management Agency. The analysis was carried out using the multiple linear regression method with the help of IBM SPSS version 26 software. The results of the study indicate that regional taxes and regional levies have a significant effect on PAD both partially and simultaneously. Therefore, optimizing tax and retribution collection policies, as well as increasing efficiency in their management, are strategic steps in supporting regional fiscal independence.